It's All In the Details: A Social Fiction Style Book Review of “Re/Invention: Methods of Social Fiction" by Patricia Leavy (2023) - Grimmett, Helen (Art/Research International)

(untitled) (University of Alberta, 2023)
Patricia Leavy’s Re/Invention: Methods of Social Fiction presents a highly readable how-to guide to writing social fiction as an accessible and impactful form of research inquiry. Providing extensive background information on the development and purposes of the genre and then discussing examples from her own social fiction novels, Leavy not only teaches readers how to go about writing social fiction but also explains why this is a worthwhile thing to do. This book review creatively puts into practice what I have learnt through reading Re/Invention. Through a fictional recounting of a book club discussion about Leavy’s work, both the form and content of this review illuminate many of the key points, tips, and techniques on offer in this highly recommended primer